Correlation of Resilience and Spatial Ability In Distance Material - Destia Wahyu Hidayati; Arie Wahyuni (Universitas Negeri Makassar, 2020)
Spatial material was material that was very useful in everyday life. Students often had difficulty in imagining spatial objects. Students would had no difficulty in imagining spatial objects if they had good spatial ability. Resilience was needed to learn spatial ability. The purpose of this study was to determine whether there was a relationship between resilience and spatial ability and how many the coefficient correlation was, and to find out dominant indicators of resilience so that there was a relationship between resilience and spatial ability in students in the upper, middle, and lower groups. This research was a qualitative-quantitative mixed research. The research instrument was used a test of spatial ability in distance and resilience scale material. The data analysis technique was used the correlation test and data triangulation method. The conclusions of this study were (1) there was a relationship between resilience and spatial ability of 56%, (2) indicators of resilience 'willing to socialize, easy to provide assistance, discuss with peers, and adapt to the environment' were dominant in the upper, middle, and lower groups , resilience indicator ‘use failure experiences to build self-motivation’ was dominant in the upper group, resilience indicators ‘show curiosity, reflect, examine, utilize a variety of dominant sources in the upper group, indicators of resilience perseverance, confidence, work hard, not easy to give up facing problems, failures and uncertainties' were dominant in the lower classes.